2008
DOI: 10.1007/s00125-008-1091-z
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and risk of microvascular complications in type 1 diabetes patients: the EURODIAB Prospective Complications Study

Abstract: Aims/hypothesis The aim of this study was to investigate the association between alcohol consumption and risk of microvascular complications (retinopathy, neuropathy, nephropathy) in type 1 diabetes mellitus patients in the EURODIAB Prospective Complications Study. Methods The EURODIAB Prospective Complications Study is a follow-up study including 3,250 type 1 diabetes mellitus patients from 16 different European countries. We investigated the cross-sectional association between moderate alcohol consumption an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 25 publications
(52 reference statements)
2
48
1
Order By: Relevance
“…some of the studies were cross-sectional and others longitudinal. Some studies, such as Xu et al [12] and Giuffre et al [14] are based on prevalence or duration of alcohol consumption while others report amounts of absolute alcohol consumed [13,15]. However, the classification of amount of alcohol consumption between studies varied considerably, and in most of them including current study, the type of alcohol being consumed has not been taken into account.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…some of the studies were cross-sectional and others longitudinal. Some studies, such as Xu et al [12] and Giuffre et al [14] are based on prevalence or duration of alcohol consumption while others report amounts of absolute alcohol consumed [13,15]. However, the classification of amount of alcohol consumption between studies varied considerably, and in most of them including current study, the type of alcohol being consumed has not been taken into account.…”
Section: Discussionmentioning
confidence: 84%
“…The association of alcohol and diabetic retinopathy does not seem to be straight-forward, since there is evidence for a U-shaped curve in the relationship between alcohol consumption and proliferative diabetic retinopathy [15], i.e. moderate drinkers are at a lower risk (OR 0.60, 95% CI 0.37-0.99) compared with heavy drinkers or abstainers Pseudo R square (Nagelkerke) was 0.366. with the association being most significant in wine drinkers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(16) Although no statistically significant association was observed between alcohol consumption and microvascular complications of diabetes mellitus, diverging of the findings of a retrospective study that showed association between these variables, (18) it is known that excessive alcohol consumption in the long term increases the incidence of complications of disease while the reduced consumption is considered a protective factor. (19) The frequency of individuals who do not smoke and who had microvascular complications was significantly higher when compared to individuals who smoked. This finding differs from results found in another study in which smokers were nearly 11 times more likely to microvascular complications.…”
Section: Discussionmentioning
confidence: 95%